2020
DOI: 10.1038/s41467-019-14000-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-specific hydrogels modulate transplanted human bone marrow-derived mesenchymal stem cell survival, engraftment, and reparative activities

Abstract: Stem cell therapies are limited by poor cell survival and engraftment. A hurdle to the use of materials for cell delivery is the lack of understanding of material properties that govern transplanted stem cell functionality. Here, we show that synthetic hydrogels presenting integrin-specific peptides enhance the survival, persistence, and osteo-reparative functions of human bone marrow-derived mesenchymal stem cells (hMSCs) transplanted in murine bone defects. Integrin-specific hydrogels regulate hMSC adhesion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 62 publications
8
99
0
Order By: Relevance
“…The best formulations showed more than twofold increases in cell proliferation on day 14 and up to threefold higher mRNA expression of relevant factors, such as angiopoietin and fibroblast growth factor-2, compared to formulations without the thermoresponsive polymer. Along with tuning mechanical properties, synthetic hydrogels with added linker molecules, including activated peptides and pro-inflammatory cytokines like IFN-γ, have also been explored as a technique to enhance MSC survival, persistence at the target site, and cytokine secretion ( 118 , 119 ). For example, hydrogels engineered with the adhesive integrin-specific peptide GFOGER compared to the nonadhesive peptide GAOGER have been shown to significantly enhance the in vitro secretion of relevant cytokines, such as IL-8 and VEGF, and subsequently enhance MSC survival, engraftment, and bone repair in an in vivo mouse bone defect model ( 118 ).…”
Section: Overcoming Clinical Challenges From Administrationmentioning
confidence: 99%
“…The best formulations showed more than twofold increases in cell proliferation on day 14 and up to threefold higher mRNA expression of relevant factors, such as angiopoietin and fibroblast growth factor-2, compared to formulations without the thermoresponsive polymer. Along with tuning mechanical properties, synthetic hydrogels with added linker molecules, including activated peptides and pro-inflammatory cytokines like IFN-γ, have also been explored as a technique to enhance MSC survival, persistence at the target site, and cytokine secretion ( 118 , 119 ). For example, hydrogels engineered with the adhesive integrin-specific peptide GFOGER compared to the nonadhesive peptide GAOGER have been shown to significantly enhance the in vitro secretion of relevant cytokines, such as IL-8 and VEGF, and subsequently enhance MSC survival, engraftment, and bone repair in an in vivo mouse bone defect model ( 118 ).…”
Section: Overcoming Clinical Challenges From Administrationmentioning
confidence: 99%
“…The influence of biomaterials on bone regeneration is mainly through the interaction between cells and surrounding biomaterials, in which interactions of cells play a main role in determining the behavior of cells on the surface of biomaterials [ 17 ]. Integrin is a heterodimeric receptor in the cell membrane, which acts as a linker between cells and substrates by binding to adhesion proteins on the surface of biological materials [ 18 ]. It is the key determinant of the subsequent cell activity including cell morphology, migration, proliferation, and differentiation.…”
Section: Hydrogels As Biomedical Materials For Btementioning
confidence: 99%
“…For example, DGEA was bound to alginate using carbodiimide chemistry and found to enhance osteogenic differentiation of mesenchymal stem cells [ 146 ]. Incorporation of GFOGER into scaffolds made from multi-arm PEG-maleimide has similarly shown that it can improve osteogenic outcomes, including the enhancement of bone repair in vivo [ 147 ]. The application of GFOGER-modified materials is not limited to bone, as such materials have also been found to support the culture and function of intestinal enteroids and endometrial spheroids [ 148 ] or mimic the tumor microenvironment [ 149 ], amongst other applications.…”
Section: Engineering Matrices From Collagen-derived Materials and mentioning
confidence: 99%